2023
DOI: 10.1039/d2va00247g
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable energy technologies for the Global South: challenges and solutions toward achieving SDG 7

Abstract: The United Nations (UN) expectations for 2030 account for a renewable, affordable, and eco-friendly energy future. The 2030 agenda includes 17 different Sustainable Development Goals (SDGs) for countries worldwide. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…The solar, hydro, wind, and other renewable energy sources have considerably reduced extreme power and environmental challenges over the last decade. [2][3][4] The power generated from solar, hydro, and wind resources needs to be efficiently stored for use whenever required. 5 Thus, attention has been paid recently to exploring sustainable and efficient energy storage systems to address the future energy demand for emerging technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The solar, hydro, wind, and other renewable energy sources have considerably reduced extreme power and environmental challenges over the last decade. [2][3][4] The power generated from solar, hydro, and wind resources needs to be efficiently stored for use whenever required. 5 Thus, attention has been paid recently to exploring sustainable and efficient energy storage systems to address the future energy demand for emerging technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The intermittent nature of renewables, such as solar and wind, poses challenges to maintaining a stable and consistent power supply. Energy storage technologies act as a vital buffer, storing excess energy during peak generation periods and releasing it when demand is high or renewable sources are unavailable [1] . Supercapacitors represent one of the most reliable and cost‐effective solutions [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Energy storage technologies act as a vital buffer, storing excess energy during peak generation periods and releasing it when demand is high or renewable sources are unavailable. [1] Supercapacitors represent one of the most reliable and costeffective solutions. [2] To enable their large-scale deployment, it is imperative to employ cost-effective, durable safe materials and electrolytes, [3] especially aqueous ones (for the latter) since they are intrinsically safe and compatible.…”
Section: Introductionmentioning
confidence: 99%
“…As an illustration, in the energy sector, blockchain holds the potential to ensure the privacy and security of energy distribution operations. 2 It would decrease the costs of interconnecting distributed energy resources in the decentralized network paradigm 3 and support the climate actions. 4 In the healthcare industry, blockchain technology offers a superior data storage system for vaccination records that would be anonymous, entrenched, and transparent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Apart from its role in the financial sector, the past decade has shown that adopting blockchain-based applications can transform different aspects of our lives. As an illustration, in the energy sector, blockchain holds the potential to ensure the privacy and security of energy distribution operations . It would decrease the costs of interconnecting distributed energy resources in the decentralized network paradigm and support the climate actions .…”
Section: Introductionmentioning
confidence: 99%